Effect of Dietary Calcium Intake and Limestone Solubility on Egg Shell Quality and Bone Parameters for Aged Laying Hens - Zhang, Bingfan; Caldas, Justina V.; Coon , Craig N. (International Journal of Poultry Science, 2017)
Background and Objective: Calcium requirement for laying hens need updated information as the genetic changes every year. Calcium are usually increased when laying hens mature in age; therefore, the objective of this study was update the calcium requirement in aged hens for optimum eggshell quality and bone strength. Methodology: Two experiments of 10 week experimental periods using 240 and 320 hens for experiment 1 and 2, respectively were conducted to study the effects of calcium intake and solubility on egg shell quality and bone status in laying hens 77-94 weeks age. Leghorn hens were randomly assigned into a 2×4×5 factorial arrangement of treatments (2 Ca sources, 4 different limestone sizes and 5 predicted calcium intake levels). Results: The findings showed that Shell Weight per Unit of Surface Area (SWUSA), egg Specific Gravity (SG), bone ash concentration and bone breaking force were significantly improved by the reduction of Limestone Solubility (LS) and higher Daily Calcium Intake (DCI) (p